Eco-friendly energy processes and technologies for achieving sustainable development - Danish, Mir Sayed Shah, 1987- (Advances in environmental engineering and green technologies (AEEGT) book series., 2021)
"This book identifies sustainability pillars such as environmental, technical, social, institutional, and economic disciplines and explores the longevity of these disciplines through a resource-oriented approach"--